High-Grade Dysplasia in Resected Main-Duct Intraductal Papillary Mucinous Neoplasm (MD-IPMN) is Associated with an Increased Risk of Subsequent Pancreatic Cancer. (March 2019) - Majumder, Shounak; Philip, Nissy A.; Singh Nagpal, Sajan Jiv; Takahashi, Naoki; Mara, Kristin C.; Kendrick, Michael L.; Smyrk, Thomas C.; Zhang, Lizhi; Levy, Michael J.; Gleeson, Ferga C.; Petersen, Bret T.; Pearson, Randall K.; et al.
Abstract : BACKGROUND: There is lack of consensus on post-operative surveillance for resected non-invasive intraductal papillary neoplasms (IPMNs). In this study we explored risk factors for subsequent PC in patients with MD-IPMN undergoing partial pancreatectomy. METHODS: We searched the Mayo Clinic surgical pathology database for all cases of resected MD-IPMN between 1997 and 2014. Cases with histologically confirmed main pancreatic duct involvement either isolated or in a mixed pattern with branch-duct involvement were included. Outcomes of PC in the remnant pancreas, and death related to MD-IPMN were assessed with survival analyses (Kaplan–Meier and Cox regression). RESULTS: Among the 179 patients with resected MD-IPMN the incidence of concomitant PC and high-grade dysplasia (HGD) in the resected specimen was 23 and 14%, respectively. The mean duration of follow-up was 4.31 years (range 0.12–13.5 years). Excluding 28 subjects who either underwent initial total pancreatectomy or partial pancreatectomy with surgical margins positive for PC/HGD, the 5-year incidence of subsequent PC was 12%, including 60.6% and 15.6% in those with initial PC and HGD, respectively. The 10-year incidence of PC was 21.2% overall, 60.6% for PC, 38.3% for HGD, and 3.0% for LGD. Risk of subsequent PC was significantly higher for those with initial PC compared with HGD (HR = 4.95, 95% CI: 1.63–15.03, p  = 0.005 and for HGD compared with LGD (HR = 11.30, 95% CI: 1.55–82.26, p  = 0.017). CONCLUSIONS: Patients with MD-IPMN with PC or HGD undergoing segmental pancreatectomy are at higher risk of subsequent PC and may benefit from post-operative surveillance. The post-operative surveillance intervals in resected MD-IPMNs need to be tailored based on dysplasia grade.